Role of Family in Forming Library Culture in Primary Class Students - Nasirovna, Dilnoza Iminova (Researchparks Publishing, 2023)
The reforms on the development of reading carried out in our country, the importance of the cooperation of pedagogues and family in the formation of the culture of reading books has been revealed.